Initiation, Continuation, Switching, and Withdrawal of Heart Failure Medical Therapies During Hospitalization - Bhagat, Aditi A.; Greene, Stephen J.; Vaduganathan, Muthiah; Fonarow, Gregg C.; Butler, Javed (JACC. Heart failure, 2019)
Patients with worsening heart failure with reduced ejection fraction (HFrEF) spend a large proportion of time in the hospital and other health care facilities. The benefits of guideline-directed medical therapy (GDMT) in the outpatient setting have been shown in large randomized controlled trials. However, the decision to initiate, continue, switch, or withdraw HFrEF medications in the inpatient setting is often based on multiple factors and subject to significant variability across providers. Based on available data, in well-selected, treatment-naïve patients who are hemodynamically stable and clinically euvolemic after stabilization during hospitalization for HF, elements of GDMT can be safely initiated. Inpatient continuation of GDMT for HFrEF appears safe and well-tolerated in most hemodynamically stable patients. Hospitalization is also a potential time for switching from an angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker to sacubitril/valsartan therapy in eligible patients, and is the subject of ongoing study. Therapy withdrawal or need for dose reduction is rarely required, but if needed identifies a particularly at-risk group of patients with progressive HF. If recurrent intolerance to neurohormonal blockers is observed, these patients should be evaluated for advanced HF therapies. There is an enduring need for using the teachable moment of HFrEF hospitalization for optimal initiation, continuation, and switching of GDMT to improve post-discharge patient outcomes and the quality of chronic HFrEF care. [Display omitted]